ANTITUMOR AND APOPTOTIC EFFECTS OF CUCURBITACIN A IN A-549 LUNG CARCINOMA CELLS IS MEDIATED VIA G2/M CELL CYCLE ARREST AND M-TOR/PI3K/AKT SIGNALLING PATHWAY. - Wang, Wen-dong; Liu, Yan; Su, Yuan; Xiong, Xian-zhi; Shang, Dan; Xu, Juan-juan; Liu, Hong-ju (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: The main aim of this study was to demonstrate the antitumor potential of cucurbitacin A on A-549 NSCLC (non-small cell lung cancer cells). The effects of Cucurbitacin A on apoptotic induction, cell physic, cell cycle failure and m-TOR/PI3K/Akt signalling pathway were also investigated in the present study. Materials and Methods: MTT assay and clonogenic assay were carried out to study effects of this compound on cell cytotoxicity and colony forming tendency in A-549 cells. Moreover, phase and fluorescence microscopic techniques were used to examine the effects on cell morphology and induction of apoptosis. The effects on cell cycle phase distribution were investigated by flow cytometry and effects on m-TOR/PI3K/Akt signalling proteins were assessed by western blot analysis. Results: Results showed that cucurbitacin A induced dose-dependent cytotoxic effects along with suppressing the colony forming tendency in these cells. Cucurbitacin A also induced morphological changes in these cells featuring chromatin condensation, cell shrinkage and apoptotic body formation. G2/M phase cell cycle collapse was also induced by Cucurbitacin A along with inhibition of expression levels of m-TOR/PI3K/Akt proteins. Conclusions: In conclusion, cucurbitacin A inhibits cancer growth in A-549 NSCLC cells by inducing apoptosis, targeting m-TOR/PI3K/Akt signalling pathway and G2/M cell cycle.